Tuberkulosis GAMBARAN KADAR ASAM URAT PADA PENDERITA TUBERKULOSIS PARU YANG MENGKONSUMSI OBAT ANTI TUBERKULOSIS (OAT) - Ulyati Ulfah (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2021)
Background : Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Most TB germs attack the lungs, but can also attack other body organs such as bones and glands. TB treatment is carried out using the DOTS strategy (Directly Observed Treatment Shortcourse) with a treatment time of 6-9 months. The DOTS strategy that uses multi-drug drugs often has side effects on the patient, such as an increase in uric acid levels in the blood.Research Objectives: The purpose of this study was to determine uric acid levels in patients with pulmonary tuberculosis (TB) who took Anti Tuberculosis Drugs (OAT) based on the length of treatment.Research Methods: This research method is descriptive by taking secondary data from Lestari Yani Manulu's research at the Special Pulmonary Hospital of Medan City in 2019.Results: The results of the study of 29 respondents who consumed OAT obtained 17 respondents (58.62%) with high uric acid levels with an average uric acid level of 9.33 mg/dl and 12 respondents (41.38%) with uric acid levels. normal with an average uric acid level of 4.90 mg/dl. Respondents with high uric acid levels consisted of 12 respondents (100.00%) with a treatment duration of 1-3 months with an average uric acid level of 6.83 mg/dl, and 5 respondents (29.41%) with a duration of treatment of 4 -8 months with an average uric acid level of 8.50 mg/dl.Conclusion: It was found that high uric acid levels in patients with pulmonary TB who took Anti Tuberculosis Drugs (OAT) were 58.62% with an average uric acid level of 9.33 mg/dl. High uric acid levels occurred in patients with intensive treatment, namely 1-3 months of 100.00% with an average uric acid level of 6.83 mg/dl.